Strategi Pemasaran Produk Paket Ibadah Haji dan Umrah di Rizkia Tour & Travel Cabang Bukittinggi - Khairil Azmi (Jurnal Riset dan Inovasi Manajemen, 2023)
The rapid development of the Haji and Umrah Travel Bureau industry at this time requires that a Haji and Umrah travel agency company must have the ability to compete. To address this, every Haji and Umrah travel agency company is required to improve its strategy in marketing its products. Because the implementation of an effective marketing strategy is one of the ways in which companies can distribute Haji/Umroh package products that suit the needs and demands of pilgrims. The purpose of this research is to analyze the marketing strategy for Haji and Umrah package products at Rizkia Tour & Travel Bukittinggi Branch. This study uses qualitative methods and belongs to field research with semi-structured interviews and documentation as data collection techniques. The findings from this study are that prospective pilgrims and Umrah pilgrims make choices about Umrah and Haji packages with considerations such as the type of Haji/Umrah packages, affordable Umrah and Haji package prices, comfort while traveling Umrah/Haji and so on.